Ground potential rise from lightning overvoltage in communication station - T. Thanasaksiri (2018)
This paper compares the ground potential rise (GPR) from lightning overvoltage with two different grounding methods, no bonding and bonding of grounding systems, between the communication tower and main ground bar (MGB) of the TOT communication station. Direct lightning stroke to the communication tower gives the higher overvoltage than the lightning stroke on distribution overhead line and also higher than the induced voltage surge. The ground bonding gives the less lightning overvoltage when compared with no ground bonding so the ground bonding in communication station is recommended. To reduce the damage from lightning overvoltage occur to the protecting equipments especially for data transmission interface (DTI), the protectors should have a higher energy discharge capability. © 2008 IEEE.